1996
DOI: 10.1136/gut.38.3.365
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal antibodies in inflammatory bowel disease are directed against intestinal bacteria.

Abstract: In contrast with normal subjects where IgA is the main immunoglobulin in the intestine, patients with active inflammatory bowel disease (IBD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
213
1
7

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(234 citation statements)
references
References 40 publications
13
213
1
7
Order By: Relevance
“…This regulatory role for SIgA has been previously inferred from correlations of IgA deficiency in humans with various autoimmune diseases and inflammatory conditions, such as celiac disease (14,15) and IBD (43). It has been suggested that IgA deficiency might result in undue triggering of the immune response to gluten in the case of celiac disease (19) and to the intestinal flora in the case of IBD (18,44), Ags to which the immune system is usually tolerant. While oral CD8 ϩ T cell tolerance to OVA was induced in pIgR Ϫ/Ϫ mice in this study, the propensity of these mice to abrogate a previously established tolerance was not investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This regulatory role for SIgA has been previously inferred from correlations of IgA deficiency in humans with various autoimmune diseases and inflammatory conditions, such as celiac disease (14,15) and IBD (43). It has been suggested that IgA deficiency might result in undue triggering of the immune response to gluten in the case of celiac disease (19) and to the intestinal flora in the case of IBD (18,44), Ags to which the immune system is usually tolerant. While oral CD8 ϩ T cell tolerance to OVA was induced in pIgR Ϫ/Ϫ mice in this study, the propensity of these mice to abrogate a previously established tolerance was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that the enteric bacterial environment has a major impact on the severity of inflammatory bowel disease (IBD), such that experimental IBD is abrogated in germ-free animals (20,21). Furthermore, the high levels of mucosal IgG Abs in UC are largely directed against intestinal bacteria (18). This suggests that intolerance to intestinal flora may trigger UC, and also that a deficiency in IgA, which is a predisposing factor in UC, might be one of the causes of this intolerance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, cervically colonized women seem to have another distribution of antibodies to different GBS epitopes than rectally colonized women, and these differences might be important for eradication of colonization. Mucosal antibodies may protect against invasive infections but still permit colonization, which is the case for commensal bacteria in the gut [31,32]. On the other hand, they may eradicate microbes from the mucosal surface, as demonstrated for Respiratory Syncytial Virus (RSV) and Haemophilus influenzae in the respiratory tract [33,34], or Vibrio cholera, Helicobacter felis and Salmonella typhimurium in the gut [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to SIgA, IgG in mucosal secretions has been reported to actively participate in the host defense against specific pathogens (8,10). In previous studies, IgG in mucosal compartments was frequently found in such pathogenic conditions as inflammatory bowel disease (11,12) and intestinal allergy (13). Mucosa-associated IgG Ab has long been known to be the only class of Ab that is actively transferred from mother to offspring to confer short-term passive immunity (14).…”
mentioning
confidence: 99%